PENGARUH LAYANAN BIMBINGAN KELOMPOK DAN LAYANAN KONSELING KELOMPOK TERHADAP PROKRASTINASI AKADEMIK SISWA KELAS XI DI SMA NEGERI 3 MANDREHE - Gulo, Desti Krisdayanti; Lase, Famahato; Rodearni Damanik, Hosianna; Foera-era Lase, Justin (IKIP Siliwangi, 2025)
The implementation of group guidance and group counseling services by school counselors is expected to be carried out in accordance with established procedural stages. This study aims to examine the significant joint influence of Group Guidance services and Group Counseling services on Academic Procrastination, as well as to investigate the partial influence of Group Guidance services on Academic Procrastination, and the partial influence of Group Counseling services on Academic Procrastination. Based on the research findings, which include validated instrument products, it can be concluded that both Group Guidance and Group Counseling services significantly influence and contribute to reducing academic procrastination. Moreover, each 1% increase in variables Group Guidance and Group Counseling is associated with a 0.937% increase in variable Academic Procrastination. These findings demonstrate that well-implemented Group Guidance and Group Counseling services are highly effective in mitigating academic procrastination among students.